Perioperative outcomes in an age-adapted analysis of the German StuDoQ|Pancreas registry for PDAC - Tschaidse, Tengis Christof; Hofmann, Felix O.; Renz, Bernhard; Hungbauer, Maximilian; Klinger, Carsten; Buhr, Heinz J.; Uhl, Waldemar; Mees, Sören Torge; Keck, Tobias; Reißfelder, Christoph; Ghadimi, Michael; D’Haese, Jan G.; et al. (BMC surgery, 2025)
Pancreatic ductal adenocarcinoma (PDAC) typically occurs in an older patient population. Yet, early-onset pancreatic cancer (EOPC) has one of the fastest growing incidence rates. This study investigated the influence of age and tumor location on postoperative morbidity and mortality in a large, real-world dataset. Patients with confirmed PDAC undergoing pancreatic surgery between 01/01/2014 and 31/12/2019 were identified from the German StuDoQ|Pancreas registry. After categorization into early- (EOPC; < 50 years), middle- (MOPC; 50 -70 years), and late-onset (LOPC; > 70 years), and stratification into pancreaticoduodenectomy (PD) or distal pancreatectomy (DP), differences in morbidity and mortality as well as clinicopathologic parameters were analyzed. In total, 3011 patients were identified. No difference in the occurrence of postoperative pancreatic fistula (POPF), postpancreatectomy hemorrhage (PPH) or delayed gastric emptying (DGE) between different age groups and resection techniques was detected. However, in patients undergoing PD, major complications (Clavien-Dindo ≥ 3a) were observed more frequently in LOPC (30,7%) than in MOPC (26,2%) and EOPC (16,9%; p < 0,01). Mortality almost tripled from EOPC (2,4%) to MOPC (3,6%) to LOPC (6,6%, p < 0,01) and significantly higher failure to rescue (FTR) rates could be observed (EOPC 14,3%, MOPC 13,6%; LOPC 21,6%; p < 0,05). In centers with DGAV certification for pancreatic surgery, the risk of complications was significantly decreased in PD (OR 0,79; 95% CI 0,65-0,94; p = 0,010). Age has a pronounced impact on the perioperative outcomes after pancreatic resections of PDAC. This effect is more prevalent in PD compared to DP. Pancreatic surgery-specific complications, such as POPF, DGE or PPH do not occur more frequently in the elderly. Overall, the risk of major complications and mortality increases in elderly patients mainly secondary to higher FTR rates.